Truncated forms of Escherichia coli lactose permease: models for study of biosynthesis and membrane insertion. - Stochaj, U (1988)
Using in vitro DNA manipulations, we constructed different lacY alleles encoding mutant proteins of the Escherichia coli lactose carrier. With respect to structural models developed for lactose permease, the truncated polypeptides represent model systems containing approximately one, two, four, and five of the N-terminal membrane-spanning alpha-helices. In addition, a protein carrying a deletion of predicted helices 3 and 4 was obtained. The different proteins were radiolabeled in plasmid-bearing E. coli minicells and were found to be stably integrated into the lipid bilayer. The truncated polypeptides of 50, 71, 143, and 174 N-terminal amino acid residues resembled the wild-type protein in their solubilization characteristics, whereas the mutant protein carrying an internal deletion of amino acid residues 72 to 142 of the lactose carrier behaved differently. Minicell membrane vesicles containing truncated proteins comprising amino acid residues 1 to 143 or 1 to 174 were subjected to limited proteolysis. Upon digestion with proteases of different specificities, the same characteristic fragment that was also produced from the membrane-associated wild-type protein was found to accumulate under these conditions. It has previously been shown to contain the intact N terminus of lactose permease. This supports the idea of an independent folding and membrane insertion of this segment even in the absence of the C-terminal part of the molecule. The results suggest that the N-terminal region of the lactose permease represents a well-defined structural domain.